The Magic Circle: Visually Representing the Woman of Endor (ovot) - Korb, Elisa (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2022)
The interaction between Saul and the woman of Endor is a minor episode, not only within the first book of Samuel, but in the Tanakh as a whole. The woman, whose actions drive the narrative, is not named nor is very much known about her. All that the text reveals are her gender, domicile location, familiarity with the law (Saul’s ban on ovot and yid’onim), and culinary possessions (flour and a calf). Through linguistic connotation her age range is surmisable: she is neither maiden nor elderly. Of her specific abilities, little is actually known as it is totally unclear what she did exactly that caused connection between the living Saul and deceased Samuel. Yet this woman, and the language used that describes her in a few verses without substantive information, have singularly driven wildly polarizing visual representations of the female thaumaturge for centuries. The artistically rendered visage of the Endoran ranges from the crone of gothic nightmares to hypersexual femme fatale, to gregarious earth mother, to occult adept perfecting her craft. Despite her shifting guise, one aspect remains consistent throughout the majority of images: the visual translation (or mistranslation) of ovot.